Insomnia pada Mahasiswa Kedokteran: Sebuah Tinjauan Pustaka - Fuad Fadillah; Lisiswanti, Rika; Rudiyanto, Waluyo; Oktafany, Oktafany (Medula, 2024)
A person who struggles to fall asleep and/or stay asleep is said to have insomnia. In Southeast Asia, 67% of 1,508 persons suffer from insomnia worldwide, and 7.3% of those who suffer from it are students. About 67% of Indonesians suffer from insomnia, with mild insomnia accounting for 55.8% and moderate insomnia for 23.3% of cases. Students who suffer from insomnia suffer, particularly those studying medicine. Medical students' usage of devices and the stress that comes with learning are linked to insomnia. By interfering with the body's sleep and wake cycle and blocking the melatonin hormone's function, using electronics at night, particularly shortly before bed, can make it difficult for the body to regulate and manage the ideal time to go to sleep and the time to be awake. Through the HPA-axis mechanism, which is triggered by corticosteroid releasing factor (CRF) and arginine vasopressin (AVP), anxiety can result in sleeplessness. This may lead the body to produce more cortisol, which would raise the wakefulness system and result in insomnia. Those who suffer from insomnia, particularly the medical students in this piece, incur unpleasant consequences. Fatigue, memory loss, and concentration issues are some of the issues that cause insomnia and impact a person's performance during the day. Disrupting concentration makes learning ineffective, which can ultimately impact medical students' performance and the quality of graduates.